The radical resection of the temporal bone - Drever, John Michael (Cirugía del Uruguay, 1976)
Baso and espino cellulary tumors are the most frequent in the externa! auditory tract. When they invade the temporal bone, the most successfu treatment is the radical excission of the bone. The authors present the surgical technique, which includes the excission of all the soft peritumoral tissues. Then, through a craneotomy, the lateral and sygmoidal sinuses are exposed, and this permits to resect the temporal bone from th! jugular forame, to the mandibular fossa. Two cases, in which thé technique was successfully used, are presented.